Cimate Emergencies vs. Sanitation - Schueler, Adriana; Carvalho, Thereza (National Journal of City Management, 2024)
It is understood here that urban development, in general and specifically in relation to basic sanitation, is not taking place adequately. Basic sanitation is seen as one of the challenges in the face of climate change, especially in terms of water resources. Extreme events, such as long periods of severe drought and extreme rainfall, are increasingly present, calling into question the resilience of infrastructure and its ability to adapt to imminent risks to human health and the environment. A field study was carried out with a visit to the Civil Defense Secretariats of Maricá and Niterói - RJ. The objective of Civil Defense is the reduction of disasters, which is the result of adverse events, natural or caused by humans, on a vulnerable ecosystem, causing human, material and environmental damage and consequent economic and social losses. The municipal secretariats of Civil Defense are the bodies that take care of the lives of citizens. It presents how the Civil Defense Secretariats are prepared to predict the weather and the heavy rains that generate urban floods and how the sewage collection network is maintained. We understand that it could be responsible for the analysis of contaminants in the waters as well.
Keywords: Flooding; Sanitation; Cities